2019
DOI: 10.1186/s12889-019-6906-y
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the link between maltreatment and delinquency: how school, family, and community factors can be protective

Abstract: Background Past experiences of childhood maltreatment are common for youth involved in the juvenile justice system. This paper explores potential protective factors at the peer, family, school, and neighborhood levels that disrupt the relationship between maltreatment and later non-violent and violent offending behavior and how these protective effects vary by a number of different sociodemographics. Methods We used data from the National Longitudinal Study of Adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 77 publications
2
13
0
4
Order By: Relevance
“…For instance, Sidebotham et al [71] and Thornberry et al [72] reported that these risk factors manifest across diverse spheres such as parental background, individual, family environment, and socioeconomic context. This finding agrees with previous studies [5,11,14,67,73]. These findings indicate the need to identify and further explore the roles of multiple risk factors for childhood adversities and their direct links to poor psychological health outcomes in the youth population with more emphasis on developing nations because the clustering of multiple risk factors increases the likelihood of ACEs [72,73].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, Sidebotham et al [71] and Thornberry et al [72] reported that these risk factors manifest across diverse spheres such as parental background, individual, family environment, and socioeconomic context. This finding agrees with previous studies [5,11,14,67,73]. These findings indicate the need to identify and further explore the roles of multiple risk factors for childhood adversities and their direct links to poor psychological health outcomes in the youth population with more emphasis on developing nations because the clustering of multiple risk factors increases the likelihood of ACEs [72,73].…”
Section: Discussionsupporting
confidence: 91%
“…This finding agrees with previous studies [5,11,14,67,73]. These findings indicate the need to identify and further explore the roles of multiple risk factors for childhood adversities and their direct links to poor psychological health outcomes in the youth population with more emphasis on developing nations because the clustering of multiple risk factors increases the likelihood of ACEs [72,73]. Also, evidence-based interventions to increase family income and improve parental education are necessary for Nigeria at the policy-making level.…”
Section: Discussionsupporting
confidence: 90%
“…Divergindo das condutas e posturas assumidas pelos professores que participaram dessa pesquisa, estudos apontam a escola como cenário propício para implementar forças que impulsionam a proteção à criança em risco ou situação de violência (Bright, et al, 2020;Del Campo & Fávero, 2020;Cordeiro, et al, 2019), e os professores como atores sociais importantes para o adequado funcionamento da rede (Macedo, et al, 2019;Wilkinson, et al, 2019).…”
Section: Discussionunclassified
“…Vislumbrado a escola como cenário potencial para a prevenção da violência contra a criança (Bright, et al, 2020;Wilkinson, et al, 2019), essa pesquisa objetivou identificar forças que interferem no enfrentamento da violência infantil pela escola. Acredita-se que dar visibilidade aos fatores que restringem e impulsionam o enfrentamento da violência pode colaborar para estratégias capazes, efetivamente, de interromper o clico da violência contra a criança e tornar a escola protagonista nesse processo.…”
Section: Introductionunclassified
“…Experiencing danger in infancy and childhood without protection and comfort by parents is therefore expected to generate more erroneous transformations than danger in adulthood (Opendak et al, 2017; Perry et al, 2017). We propose that facing danger with outdated or erroneous transformations lies at the root of mental illness, child maltreatment and criminality (Baetz and Widom, 2020; Crittenden, 1999; Wilkinson et al, 2019). That is, danger itself does not lead to maladaptive behaviour or psychological trauma; instead, erroneous information about danger creates these risks.…”
Section: Part 1: a Model Of Adaptation And Maladaptationmentioning
confidence: 99%